Formation of Influenza Virus Proteins - Klenk, Hans-Dieter (1973)
Eight virus-specific proteins have been found in chicken embryo fibroblasts infected with fowl plague virus. Among them are two glycoproteins which are the constituents of the hemagglutinin on the virus particle. They are derived from a large precursor glycoprotein by cleavage of a covalent linkage. The reaction can be blocked by the protease inhibitor diisopropylfluorophosphate and the amino acid analogue fluorophenylalanine. This indicates that a peptide bond is cleaved. If infected cells are kept at 25 C, a temperature at which virus maturation is inhibited, the precursor glycoprotein is cleaved at a significantly slower rate than at 37 C. It appears, however, that a reduced synthesis of the carbohydrate-free envelope protein is responsible for the block of virus maturation at 25 C rather than the lower cleavage rate of the precursor.